Tecendo fios, fazendo história: a atuação operária na Cidade-Fábrica Rio Tinto (Paraíba, 1959-1964) - Vale, Eltern Campina (2008)
This essay studies the workers’ collisions in the period of 1959 through 1964, emphasizing the labour movement in Paraíba. It approaches, initially, the construction of the Rio Tinto Factory, between the years of 1917 and 1924, undertaking described in the press and in memoirs as a great enterprise, since, in their vision, the factory developed the economy of the region and of Paraíba. The first strikes in 1930, the creation of the worker’s union in 1932, the watch and repression of the communist labourers, and also the paralyzations in 1946 and 1951, are studied here as classes’ experiences, in its organizational process, and in its contents of heritage and division. It accentuates the ascension of the workers’ organization in Rio Tinto between 1959 and 1964, as an essential center of the labour movement in Paraíba, putting into practice their agenda of demands, conquering victories, suffering reverses and articulating in the electoral politics. The analysis of the workers’ processes, as a way of conquering rights, identifies the labour issues as an expression of the workers’ struggle. It is also studied the conjuncture of 1960, with the election of the labourer Antônio Fernandes for the union and for the city hall of the factorytown in 1963, and the repression of the labour movement in Rio Tinto after the coup d’état civil-military of 1964.